2019
DOI: 10.1088/1367-2630/ab5cb3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of the negative thermal expansion in zinc-blende and diamond-like semiconductors

Abstract: Upon heating, almost all zinc-blende (ZB) and diamond-like semiconductors undergo volume contraction at low temperature, i.e. negative thermal expansion (NTE), instead of commonly expected expansion. Specifically, CuCl has the largest NTE among these semiconductors with a coefficient comparable with the record value of ZrW 2 O 8 . So far, underlying physical mechanism remains ambiguous. Here, we present a systematic and quantitative study of the NTE in ZB and diamond-like semiconductors using first-principles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…As displayed in Fig. 4a, we find that the lattice vibrational potential energy of CuCl increases as U rises, due to the reduced s-d coupling strength resulting from the lowering of Cu 3d energy level and accompanied wave func-tion localization [45][46][47] (Fig. S7).…”
Section: Harmonic Vibrationsmentioning
confidence: 83%
See 1 more Smart Citation
“…As displayed in Fig. 4a, we find that the lattice vibrational potential energy of CuCl increases as U rises, due to the reduced s-d coupling strength resulting from the lowering of Cu 3d energy level and accompanied wave func-tion localization [45][46][47] (Fig. S7).…”
Section: Harmonic Vibrationsmentioning
confidence: 83%
“…In copper-based semiconductors such as copper halides, the copper's 3d orbital dominates the valence band maximum (VBM) state and is below the s-like conduction band minimum (CBM) by a band gap (about 3-4 eV) (Fig. S3) [45][46][47] . The small energy difference between copper's 3d and 4s states enhances their coupling which lowers the lattice vibrational potential energy.…”
Section: Harmonic Vibrationsmentioning
confidence: 99%
“…These calculated negative mode Grüneisen parameters in the B3 phase for the TA modes at X and L special points could be interpreted as a signal for a potential dynamical instability but our phonon calculations at high pressures discussed above do not confirm this hypothesis. In this respect, it is interesting to note that the presence of negative mode Grüneisen parameters in other zinc blende (B3) and diamond-like semiconductors is considered as a necessary condition for the presence of the negative thermal expansion at low temperatures 54 although a study of this phenomenon in SiC is out of the scope of the present work.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging halide perovskite is likely the most potential candidate for next-generation solar cell materials, as it is found that the PCE of halide perovskites has increased from 3.8% to 25.2% over the past decade. 9,12 Although the record module efficiency of halide perovskite is 16.1%, lower than that of polysilicon solar cell, 10 it can be fabricated by simple and low-cost ink-jet printing [13][14][15][16] and blade coating [17][18][19][20] techniques. However, for commercialization one must solve the issue of halide perovskite stabilities.…”
Section: Introductionmentioning
confidence: 99%